INDUKSI PEMBUNGAAN TANAMAN VANILI SECARA MEKANIS DENGAN PEMANGKASAN KIMIA MENGGUNAKAN PACLOBUTRAZOL DAN APLIKASI TRICHODERMA - Suryanti, S.; Widyasaputra, R.; Mawandha, H.G.; Himawan, A. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana Mengabdi, 2023)
Vanilla ( Vanilla planifolia  Andrews) is a plantation commodity with high economic value and has long been developed by the Ayem farmer group  in Sinogo Village  through the Mbajing Learning House (Rube).  In their cultivation, vanilla farmers in Sinogo Village have problems in making plants stressed ( stressing  periods) so that plants can not bloom.  Therefore,  community service activities are carried out regarding the induction of vanilla flowering.  With this PKM  activity, it is hoped that farmers can understand and apply  the correct vanilla cultivation techniques and apply several flowering induction  techniques.   This is done because from hasil survey conducted shows that 100% of vanilla farmers of Sinogo Village in vanilla cultivation still use local varieties. Sinogo farmers were not yet familiar with the high-yielding varieties of vanilla produced by the Ministry of Agriculture. The planting medium used soil, cocopit and manure. The flowering induction technique  that  has been carried out  was only  mechanically by trimming the tendrils so that when the rainfall  is high, the flower stressing  does not work. There were PKM activities carried out counseling on superior varieties of vanilla, correct vanilla cultivation  techniques and several flowering induction techniques,  namely mechanically by  means of prunning, chemically  using paclobutrazol and biologically using  the fungus  Trichoderma . Keywords : Induction, Flowering, Vanilla, Cutting, Paclobutrazol, Trichoderma